1795 Did Ventilatory Strategy Change During the Last 5 Years in Italian Neonatal Network?. (October 2012) - Vendettuoli, V; Condò, M; Poloniato, A; Raia, M; Ramacciato, F; Tina, LG; Abbiati, LM; Staffler, A; Agostiniani, S
Abstract : Background: Intubation and mechanical ventilation (MV) are life-saving procedures but are associated with a higher incidence of acute and chronic complications. Thus, non-invasive ventilation (NIV: nasal continuous pulmonary distending pressure, nasal ventilation, or high-flow nasal cannula) is increasingly used. Aim: To evaluate changes in ventilatory strategies between 2006 and 2010 in Italian neonatal network (INN). Methods: A cohort of neonates < 30 weeks gestational age (GA) or < 1501 g birth weight (BW), without congenital anomalies, born in 2006 and 2010, assisted in 31 hospitals participating in INN both years, was analysed (N=3459: 1713 in 2006, and 1746 in 2010). Variables were defined according to Vermont-Oxford network. Logistic regressions, adjusting for confounders (GA, BW for GA, antenatal steroids, mode of delivery, multiple pregnancy, 1-minute Apgar score, being inborn, sex, intubation in delivery room, RDS, PDA), and clustering for hospitals, were used. Results: Between 2006 and 2010 there were no changes in GA or BW (2006: mean GA 29.1 wks; BW 1087 g; 2010: GA 29.2 wks; BW 1083 g), while antenatal steroids increased (from 78.5% to 83.5%). The number of infants receiving any ventilatory support increased from 81.8% to 85.9%. After adjusting for confounders, mortality decreased (Odds ratio=0.75, 95% confidence interval 0.57–0.98) as well as mechanical ventilation (OR=0.72, 95%CI 0.57–0.90) and BPD (OR=0.68, 95%CI 0.54–0.86), while NIV increased (OR= 1.70, 95%CI 1.41–2.04). Conclusions: In the last 5 years, we observed a reduction of MV and an increase of NIV use. This was accompanied by a decrease in risk-adjusted mortality and BPD.